Review of Macroeconomic Methods and Microeconomic Valuation Methods Applied in the Natural Resources and Environment Sector - Danilo C. Israel (Philippine Institute for Development Studies (PIDS), 1994)
The analysis of micro impacts of macroeconomic adjustment policies (MIMAP) has been extended to the environment and natural resources sectors. This research is devoted for the review of the different macroeconomic models and microeconomic valuation methods in the analysis of the sector. In particular, this reviews the empirical works in the Philippines using these methods. Identification of analytical approaches and areas for research in the sector, which are useful for the MIMAP project, is conducted.
Keywords: 330; natural resources and environment; computable general equilibrium (CGE); input-output framework; environmental issues; MIMAP; macroeconomic adjustments; Kedaong Injection; econometric modeling